Strategi Pemasaran dalam Upaya Meningkatkan Usaha Mandiri Penjualan Parfum pada Parfum Premium Bekasi - Bhiba, Sarah; Wilis, Ratih; Setyadi, Yusuf (Universitas Methodist Indonesia, 2025)
Marketing strategy requires a combination of understanding the market, creativity in promotion, attention to product quality standards, and responsiveness to market changes where marketing strategy is the main driver. Overcoming barriers to harnessing the power of digital marketing through social media such as Instagram with its online advertising can help with strong brand awareness where consumer satisfaction is the focus. Preferences and promotions are created to build attractive loyalty programs and retain existing consumers with special offers, discounts or limited-time promotions to encourage repeat purchases and create consumer loyalty for future marketing strategies. This study aims to analyze descriptively qualitatively the marketing strategies, constraints, and solutions used in increasing sales in perfume sales independent business products located in Parfum Premium Bekasi, Indonesia. Data collection techniques use structured interview techniques on active consumers and direct observation in the field of consumer behavior when shopping online. Data analysis using SWOT (Strengths, Weaknesses, Opportunities, and Threats) analysis techniques. The results showed that Parfum Premium Bekasi's independent business has been considered quite successful in sales growth, strengthening its position in the competitive perfume market, and providing a satisfying experience for customers, especially the use of online media in the form of Instagram which can increase sales. Obstacles include lack of product innovation and variety offered, changes in product or service quality, and economic changes that affect customer preferences. The solution to the problem is to understand customer preferences and market trends to increase buying interest through intensive monitoring of product quality and customer service.